Small Ball Games as a Motor Skill Intervention for Students with Moderate Intellectual Disability - Raden Sukis Hariyanto; Nada Nabhan Ismail; Murtada Hasoon; Nedal Abu AlFailat (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aims to examine the effectiveness of small ball games as a physical education intervention for improving motor skills among students with moderate intellectual disability in an Indonesian special needs school setting. Methodology: This study employed a Classroom Action Research (CAR) design consisting of two cycles conducted with eight Grade III students with moderate intellectual disability at SLB Negeri Kendal, Central Java. Data were collected through motor performance tests, participatory observation, documentation, and teacher interviews. Data validity was established using triangulation techniques, while learning achievement was evaluated based on individual and classical mastery criteria. Main Findings: The findings showed progressive improvement in students’ motor skills across both action research cycles. Mean motor performance scores increased from baseline to Cycle 1 and further improved in Cycle 2, while classical completion rates exceeded the established mastery target. Observational results also confirmed enhancement in running and walking command comprehension, ball catching, and ball bouncing abilities through structured small ball game activities. Novelty/Originality of this study: This study demonstrates the effectiveness of small ball games as an adaptive and low-cost intervention for enhancing motor development in students with moderate intellectual disability. The research provides a practical and replicable play-based instructional model for adapted physical education in Indonesian special needs schools, emphasizing sequential and command-based motor learning strategies